Effect of Enhanced Medical Rehabilitation on Functional Recovery in Older Adults Receiving Skilled Nursing Care After Acute Rehabilitation: A Randomized Clinical Trial - Lenze, Eric J. (JAMA Netw Open, 2019)
IMPORTANCE: Enhanced medical rehabilitation (EMR) is a systematic and standardized approach for physical and occupational therapists to engage patients. Higher patient engagement in therapy might lead to improved functional recovery in rehabilitation settings, such as skilled nursing facilities (SNFs). OBJECTIVE: To determine whether EMR improves older adults’ functional recovery. DESIGN, SETTING, AND PARTICIPANTS: A double-blind, parallel-group, randomized clinical trial was conducted from July 29, 2014, to July 13, 2018, in 229 adults aged 65 years or older admitted to 2 US SNFs. Participants were randomized to receive EMR (n = 114) vs standard-of-care rehabilitation (n = 115). Intention-to-treat analysis was used. INTERVENTIONS: The intervention group received their physical and occupational therapy from therapists trained in EMR. Based on models of motivation and behavior change, EMR is a toolkit of techniques to increase patient engagement and therapy intensity. The control group received standard-of-care rehabilitation from physical and occupational therapists not trained in EMR. MAIN OUTCOMES AND MEASURES: The primary outcome was change in function in activities of daily living and mobility, as assessed with the Barthel Index, which measures 10 basic activities of daily living or mobility items (scale range, 0-100), from SNF admission to discharge; secondary outcomes were gait speed for 10 m, 6-minute walk test, discharge disposition, rehospitalizations, and self-reported functional status at days 30, 60, and 90. To examine the rehabilitation process, therapists’ engagement with patients and patient active time during therapy were measured for a sample of the sessions. RESULTS: Of the 229 participants, 149 (65.1%) were women; 177 (77.3%) were white, and 51 (22.3%) were black; mean (SD) age was 79.3 (8.0) years. Participants assigned to EMR showed greater recovery of function than those assigned to standard of care (mean increase in Barthel Index score, 35 points; 95% CI, 31.6-38.3 vs 28 points; 95% CI, 25.2-31.7 points; P = .007). There was no evidence of a difference in the length of stay (mean [SD], 23.5 [13.1] days). However, there were no group by time differences in secondary outcome measures, including self-reported function after SNF discharge out to 90 days as measured on the Barthel Index (mean [SE] score: EMR, 83.65 [2.20]; standard of care, 84.67 [2.16]; P = .96). The EMR therapists used a median (interquartile range) of 24.4 (21.0-37.3) motivational messages per therapy session vs 2.3 (1.1-2.9) for nontrained therapists (P < .001), and EMR patients were active during a mean (SD) of 52.5 (6.6%) of the therapy session time vs 41.2 (6.8%) for nontrained therapists (P = .001). CONCLUSIONS AND RELEVANCE: Enhanced medical rehabilitation modestly improved short-term functional recovery for selected older adults rehabilitating in SNFs. However, there was no evidence that the benefits persisted over the longer term. This study demonstrates the value of engaging and motivating older adults in rehabilitation therapy, but more work is needed to extend these benefits to longer-term outcomes after discharge home. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02114879